Carbono almacenado en la biomasa de las especies forestales de la parcela VII del arboretum "El Huayo" del Centro de Investigación y Enseñanza Forestal, Puerto Almendra, Iquitos, 2021 - Valdivia Acho, Kattery Valerie (2022)
The research was conducted in plot VII of the Arboretum "El Huayo" of the Center for Research and Forestry Education, where the biomass was quantified giving a total of 401549.83 kg in the forest species of the plot, whereby the species Eschweleira coriaceae (DC) S.A. Mori quantifies the highest biomass with 60603.10 kg and followed by Cariniana coriaceae with 28010.16 kg of biomass. Mori quantifies the highest biomass with 60603.10 kg and followed by Cariniana decancra with 28010.16 kg of biomass and also was obtained as a result the quantification of carbon stored with a total of 200.77 tC in the biomass of forest species, it was given that the highest storage occurred in the Eschweleira coriaceae (DC) S. A. Mori quantifies 30.00 kg of biomass in the plot. A. Mori quantifies 30.30 tC and Cariniana decancra with 14.01 tC of biomass, both species belong to the Lecythidaceae family. The normality test was performed, indicating that the data do not follow a normal distribution, since the p-value is 0.000, which is lower than the significance level of 0.05, which led to use the non-parametric Kruskal-Wallis test, resulting in a p-value of 0.482, which is higher than the significance level of 0.05, therefore, the null hypothesis is accepted, which states that there is no difference between biomass and carbon stored in the forest species evaluated.